2011
DOI: 10.1007/s00436-011-2504-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fasciola hepatica proteins on the functioning of rat hepatocytes

Abstract: Fasciolosis is a hepatic parasitic infection that affects many mammal species and creates a great economic and veterinary problem. Molecular mechanisms of parasite–hepatocyte interactions have not been precisely characterized yet. Therefore, the aim of the study was to investigate alterations in the metabolic activity of rat liver cells exposed to Fasciola hepatica somatic proteins. Hepatocytes were incubated with 0–1 mg/ml of fluke's somatic proteins for various periods of time. Afterward, changes in hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our results are consistent with those achieved by Gajewska et al (2006) who showed that rat hepatocyte cell death is caused by FhES products. Similar results have also been obtained when rat liver cells were treated with homogenate of adult F. hepatica (Wesołowska et al 2012). Several proteomic studies on the composition of F. hepatica ES have been undertaken in recent years, and numerous proteins have been found in adult F. hepatica ES, the most abundant of which appear to be the cathepsin L proteases which have been shown to digest basement membrane and extracellular matrix proteins including collagen, fibronectin and laminin, suggesting Fasciola hepatica ES (A) produced dose-dependent death of Hep-G2 cells, whereas this effect was not observed for cells treated with FhPGK (B) Cytotoxicity of Fasciola hepatica ES 217 roles in migration (Berasain et al 1997;Norbury et al 2011).…”
Section: Human Hepatocyte F Hepatica Es Recombinant Fhpgksupporting
confidence: 85%
See 2 more Smart Citations
“…Our results are consistent with those achieved by Gajewska et al (2006) who showed that rat hepatocyte cell death is caused by FhES products. Similar results have also been obtained when rat liver cells were treated with homogenate of adult F. hepatica (Wesołowska et al 2012). Several proteomic studies on the composition of F. hepatica ES have been undertaken in recent years, and numerous proteins have been found in adult F. hepatica ES, the most abundant of which appear to be the cathepsin L proteases which have been shown to digest basement membrane and extracellular matrix proteins including collagen, fibronectin and laminin, suggesting Fasciola hepatica ES (A) produced dose-dependent death of Hep-G2 cells, whereas this effect was not observed for cells treated with FhPGK (B) Cytotoxicity of Fasciola hepatica ES 217 roles in migration (Berasain et al 1997;Norbury et al 2011).…”
Section: Human Hepatocyte F Hepatica Es Recombinant Fhpgksupporting
confidence: 85%
“…It is now known that FhES components can induce alternatively activated macrophages (Donnelly et al 2005;Flynn et al 2007), and apoptosis of peritoneal macrophages (Guasconi et al 2012) and eosinophils (Serradell et al 2009). There are only limited data concerning the effects of F. hepatica proteins on hepatocytes; it has been shown that both somatic (Wesołowska et al 2012) and FhES (Gajewska et al 2006) fractions influence survival of rat hepatocytes in vitro. In this study we determined the cytotoxic potential of FhES and the strictly intracellular protein -phosphoglycerate kinase (FhPGK) on Hep-G2 cells (a human hepatocyte cell line).…”
Section: Human Hepatocyte F Hepatica Es Recombinant Fhpgkmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest ALP activity is found on the border membranes of the bile duct whereas GGT is found in the hepatocytes and biliary epithelial cell [ 8 , 12 ]. Increased level of these enzymes is an indicator of hepatobiliary injury, epithelial damage and stasis of the bile duct [ 8 , 17 , 27 ]. There are many previous studies on serum liver enzymes of sheep, cattle and monkey infected with F. hepatica and F. gigantica, but few on dynamics of serum liver enzymes in rabbit fascioliasis [ 5 , 6 , 7 , 9 , 17 , 24 , 25 , 29 ].…”
mentioning
confidence: 99%
“…The resultant uncontrolled and excessive production of IL‐1κ mediates several proinflammatory disorders with severe pathologic outcomes (37). The migration of F. he‐ patica through the host's liver results in significant tissue damage (38, 39), and the parasite's secretions can induce hepatocyte cell death (40, 41). Inflammation and fibrosis in the liver is typically associated with excessive NLRP3 inflammasome activity, culminating in hepatocyte destruction via pyroptosis and IL‐1β secretion (42).…”
Section: Discussionmentioning
confidence: 99%